"I Love This Book Because That's Like Me!" A Multilingual Refugee/Adolescent Girl Responds From Her Homeplace. Issue 4 (2nd October 2017) - Stewart, Mary Amanda
ABSTRACT: Research acknowledges the value of youths reading books that represent their lives and cultures, yet there is a growing need to better understand how youths of understudied groups respond to multicultural stories. This single-case study of a multilingual refugee adolescent from Burma (Myanmar) investigates how she draws from her lived experiences in responding to literature. Using the culturally situated reader response model (Brooks & Browne, 2012) to understand the participant's response to literature allows us to see how her transaction with the texts was mediated by various aspects of her lived experiences as a refugee and adolescent girl. The participant's powerful response is indicative of not just the need for relevant literature but also authentic ways to respond with a caring adult. Findings suggest that far more important than new programs or strategies, multilingual youths need access to relevant literature and authentic meaning-making for educators to most effectively nurture their literacy, language, and identity development.